Inside Back Cover: Adaptive Lipid Immiscibility and Membrane Remodeling Are Active Functional Determinants of Primary Ciliogenesis (Small Methods 2/2021). Issue 2 (12th February 2021) - Bernabé‐Rubio, Miguel; Bosch‐Fortea, Minerva; García, Esther; Bernardino de la Serna, Jorge; Alonso, Miguel A.
Abstract : In article number 2000711 by Jorge Bernardino de la Serna, Miguel A. Alonso, and co‐workers, a method developed to track space‐time lipid self‐assembly in live cells by simultaneously determining lateral lipid packing and micro‐ and nanoscale dynamics, reveals that the condensed nano‐ and micro‐domains associated with the midbody remnant are remodeled and they actively self‐assemble to provide lipids to the centrosome for ciliary membrane assembly, a fundamental as yet unsolved biological process.